Are price controls necessarily bad? The case of rice in Vietnam - Madanmohan Ghosh; John Whalley (The University of Western Ontario, Department of Economics, 2002)
Most economists' instinctive reaction to price controls is that they are harmful. If enforced, they result in shortages and resource misallocation. With weak enforcement they often result in black markets, and high transaction costs. In this paper we assess the pros and cons of rice price controls in Vietnam given these instincts. We argue that these price controls fix producer prices and allow government marketing agencies to sell at higher prices and hence are, in part, a revenue raising device. As such they may be part of an efficient tax mix, particularly so since agricultural incomes and production go untaxed under the formal tax system. We also argue that such controls can act to dampen costly domestic adjustments in the face of volatile world prices. We develop a multi sector multi household general equilibrium model to numerically analyse the consequences of these price controls, and show that this system can be supported as welfare enhancing under conditions which currently prevail in the Vietnamese economy. The case against price controls may hold in other circumstances, but in this case the arguments seem to be more nuanced.
Keywords: D2; D4; D5; D6; H2; H3; 330; Price controls; General Equilibrium; Tax-mix; Rice; Vietnam